Undeclared - Higgins, Chris (The MIT Press, 2024)
An imaginative tour of the contemporary university as it could be: a place to discover self-knowledge, meaning, and purpose.What if college were not just a means of acquiring credentials, but a place to pursue our formation as whole persons striving to lead lives of meaning and purpose? In Undeclared, Chris Higgins confronts the contemporary university in a bid to reclaim a formative mission for higher education. In a series of searching essays and pointed interludes, Higgins challenges us to acknowledge how far our practices have drifted from our ideals, asking: What would it look like to build a college from the ground up to support self-discovery and personal integration? What does it mean to be a public university, and are there any left? How can the humanities help the job-ified university begin to take vocation seriously? Cutting through the underbrush of received ideas, Higgins follows the insight where it leads, clearing a path from the corporate multiversity to the renaissance in higher education that was Black Mountain College and back again. Along the way, we tour a campus bent on becoming a shopping mall, accompany John Dewey through a midlife crisis, and witness the first "happening.” Through diverse and grounded philosophical engagements, Undeclared assembles the resources to expand the contemporary educational imagination.